2020
DOI: 10.1364/ol.399053
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of single-mode topological valley-Hall lasing at telecommunication wavelength controlled by the degree of asymmetry

Abstract: Topology plays a fundamental role in contemporary physics and enables new information processing schemes and wave device physics with built-in robustness. However, the creation of photonic topological phases usually requires complex geometries that limit the prospect for miniaturization and integration and dispossess designers of additional degrees of freedom needed to control topological modes on-chip. By controlling the degree of asymmetry (DoA) in a photonic crystal with broken inversion symmetry, we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…Our results reveal the role of interface effects in forming gapless chiral edge (kink) states and expand how we can exploit valley DOF and engineer valleytronic devices. This includes new opportunities to develop low-loss compact delay lines 11 , on-chip isolation, slow-light optical buffers, and lasers 10,33 . Lastly, the waveguiding phenomenon demonstrated here is applicable not only to the electromagnetic spectrum and various optical systems, but also to other wave systems such as plasmonics, mechanics and acoustics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results reveal the role of interface effects in forming gapless chiral edge (kink) states and expand how we can exploit valley DOF and engineer valleytronic devices. This includes new opportunities to develop low-loss compact delay lines 11 , on-chip isolation, slow-light optical buffers, and lasers 10,33 . Lastly, the waveguiding phenomenon demonstrated here is applicable not only to the electromagnetic spectrum and various optical systems, but also to other wave systems such as plasmonics, mechanics and acoustics.…”
Section: Resultsmentioning
confidence: 99%
“…This has changed with the advent of PTIs [13][14][15][16][17][18][19][20][21][22][23][24] , which, like their electronic counterparts 25 , enable backscattering-immune edge modes along almost arbitrarily shaped interfaces. Among the three basic topological phases -quantum Hall 26 , quantum spin-Hall 27, 28 , and quantum valley-Hall 29,30 topological insulators-the latter, which relies on the valley degree of freedom (DOF) 1 in crystals is arguably the easiest to implement in bosonic systems 2,[5][6][7][8][9][10][11][31][32][33] and is of the most interest to the development of on-chip optical devices, motivating of this work.…”
Section: Mainmentioning
confidence: 99%
“…The topological cavities have also been proved to be very useful for topological lasers. [ 32,120–123 ] In the previous study, [ 32 ] Zeng et al demonstrated a terahertz QCL based on the topological cavity with sharp corners (see Figure a). The QCLs are compact, electrically pumped semiconductor lasers operating at the mid‐infrared and terahertz frequencies.…”
Section: Topological Cavities and Lasersmentioning
confidence: 99%
“…The topological valley‐Hall lasers at optical frequencies have also been investigated experimentally in the previous studies. [ 120,121 ] In the previous study, [ 120 ] the authors realized a room‐temperature laser from the triangle‐shaped topological cavities formed by two domains of VPCs with opposite valley‐Chern numbers (Figure 11c). Different from other works, the previous study [ 120 ] identified a unique triade lasing mode whose emission exhibits hot spots at the three corners of the cavity (see Figure 11d).…”
Section: Topological Cavities and Lasersmentioning
confidence: 99%
See 1 more Smart Citation